Preoperative clonidine or levobupivacaine : effect on systemic inflammatory stress response - Peršec, Jasminka (Array, 2009)
Abstract: With perioperative pain control it is possible to supervise immune system, release of inflammation mediators, and influence on treatment outcome. Use of analgetics before the pain stimulus (preventive analgesia) obstruct development of neuroplastic changes in central nervous system, and reduces pain. Investigation hypothesis was that preoperative epidural clonidine is more efficient in blockade of systemic inflammatory stress response comparing to levobupivacaine. Patients were allocated to three groups, according to preoperative epidural use of clonidine, levobupivacaine or saline (control group). Before operation, 1 h after the beginning, 1 h, 6 h, 12 h and 24 h after the operation following parameters were analyzed: interleukine-6, C-reactive protein and leukocyte count. There were no significant differences between groups in age, gender, body mass index and operation time. In preoperative clonidine group, we found significant reduction in interleukine-6 levels throughout investigation time, compared to preoperative levobupivacaine group and control group. Also, C-reactive protein was significantly lower at the end of investigation, compared to other two groups. Leukocyte count was lower, and within the normal range in all investigation times only in preoperative clonidine group. We demonstrated significant difference that support importance of clonidine central effect on pain pathways and systemic inflammatory blockade